The livelihood of Rickshaw Pullers in Dhaka City During Covid-19 Pandemic: A Social Review - Talukder, Md. Towhidul Islam; Monwar, Mohammad Mostafa; Sultana, Shanjida; Babui, Moshiur Rahman; Siddique, Sazid (British Journal of Healthcare and Medical Research, 2023)
Introduction: A rickshaw puller is a worker who makes a living by pulling rickshaws. A rickshaw puller’s main task is to transport passengers and goods from one location to another. Their lives are fraught with difficulties. Because of the epidemic condition, the majority of Dhaka’s rickshaw pullers are experiencing unemployment and joblessness. The majority of rickshaw pullers are the primary breadwinners in their families. They spend their lives based on their daily earnings; thus, they must pull their rickshaw. Aim of the study: The study aimed to observe the lifestyle of rickshaw pullers during the Covid-19 pandemic, focusing on their livelihood. Methods: This cross-sectional quantitative analytical study was conducted targeting rickshaw pullers of dhaka city only. The study was conducted in a 1-year period, from february 2021 to january 2022, with a total of 200 rickshaw pullers from 3 places in dhaka city, badda, mirpur, and Bashundhara. Result: 55% of the participants were the sole earner in the family, 90% had been married, and only 12% had owned their rickshaws. 96% of participants lived in financial deficiency, 70% had been living in debt, and only 1% had savings. The average work day was 8-10 hours long for the majority (61%) of participants, 89% did not have a habit of wearing a facemask. Among the 178 participants who did not wear face masks, 91.01% cited difficulty in breathing during rickshaw pulling as the cause, while 7.87% said that masks were costly. 96% of participants had a significant decrease in their income. Conclusion: during the statewide shutdown induced by the covid-19 epidemic, the income of rickshaw pullers in the capital decreased. Rickshaw drivers live hand to mouth. They endure regular challenges at work due to limits on their operations such as harassment from passengers and traffic cops.